Reabilitação oral com facetas diretas em paciente com manchamento dental por tetraciclina : relato de caso - Rozado, Janyce Bezerra (2020)
Tetracyclines are broad spectrum antibiotics that can be used to treat common infections in children and adults, and can cause discoloration and hypoplasia of tooth enamel in deciduous and permanent dentition if administered during the period of dental development. Patients with tetracycline dental staining tend to have significant complaints and dissatisfaction. Therefore, this paper aims to describe the case of oral rehabilitation with direct composite resin veneers in a patient with tetracycline dental staining. Patient C.F.N, male, normossystemic, 40 years old, attended the São João Calabria Dental Complex, at the Catholic University Center of Quixadá, in the municipality of Quixadá, complaining: “of discomfort with dark teeth”. Extra-oral physical examination revealed nothing out of the ordinary. The intra-oral clinical examination showed a reddish-pink staining of the soft tissues, indicating a healthy state. In addition, some gingival retractions and noncarious cervical lesions located on teeth 16 and 26 were noted; dental fracture in tooth 11, affecting the angle of this incisal; and finally, tetracyclines grade 2 stains were observed, where they had a moderate color, ranging from brownish-yellow to dark gray. Thus, a treatment plan was established for the patient, and oral adequacy procedures and direct restorations were performed to improve dental function and aesthetics. Finally, it can be concluded that oral rehabilitation with direct facets made it possible to restore smile harmony, favoring increased self-esteem, well-being and patient satisfaction.